Successful endovascular embolisation of a jejunal artery aneurysm - Lo, Zhiwen Joseph (Singapore Med J, 2015)
Jejunal artery aneurysms are rare, with only six cases reported in the literature to date. Endovascular embolisation of the jejunal artery is rarely performed. Herein, we report the case of a 57-year-old man who successfully underwent endovascular embolisation for bleeding caecal diverticulosis, during which a 9-mm fusiform jejunal artery aneurysm was incidentally diagnosed. Subsequently, the jejunal aneurysm was successfully embolised using Vortex coils.